Growth and reforms in centrally planned economies : the lessons of the Bulgarian experience - Feiwel, George R. (New York : Praeger Publishers, 1977)
This book attempts to find an answer to the question of whether this faster growth is not counterbalanced by the increasing gap between the rates of growth of national product and net economic welfare. The book is divided into nine chapters and is completed with a statistical appendix and selected bibliography. Titles of the chapters are: (1) High-Pressure Economy. (2) Growth and Instability. (3) Resources Utilization. (4) Economic Reform; Transitional Period. (5) Prices and Decisions. (6) Redesign of the System. (7) Continuity and Change. (8) Accent on Living Standards? and (9) Planning Philosophies and Reforms.
Bibliography: p. 338-345.
lje 12/12/18
Loans
Keywords: Economic growth; Economic development; Bulgaria